Matrix metalloproteinase 7 contributes to intestinal barrier dysfunction by degrading tight junction protein Claudin-7 - Xiao, Ying; Lian, Haifeng; Zhong, Xiaoying S.; Krishnachaitanya, Srikruthi S.; Cong, Yingzi; Dashwood, Roderick H.; Savidge, Tor C.; Powell, Don W.; Liu, Xiaowei; Li, Qingjie (Frontiers in Immunology, 2022)
Background: Previous studies implicated matrix metalloproteinases (MMPs), such as MMP-7, in inflammatory bowel diseases (IBD) by showing increased activity during inflammation of the gut. However, the pathophysiological roles of MMP-7 have not been clearly elucidated. Methods: The expression of MMP-7 was assessed in colonic biopsies of patients with ulcerative colitis (UC), in rodents with experimental colitis, and in cell-based assays with cytokines. Wild-type and MMP-7-null mice treated with dextran sulfate sodium (DSS) or trinitrobenzene sulfonic acid were used for determining the pro-inflammatory function(s) of MMP-7 in vivo. Results: MMP-7 was highly expressed in patients with UC and in rodents with experimental colitis. IL-1β, IL-4, IL-13, TNFα, or lipopolysaccharide enhanced MMP-7 expression in human colonic epithelial cells, rat colonic smooth muscle cells, and THP-1-derived macrophages. Active MMP-7 degraded tight junction protein Claudin-7 in epithelial cells, cleaved recombinant Claudin-7 in cell-free system, and increased Caco-2 monolayer permeability. Immunostaining of colon biopsies revealed up-regulation of MMP-7 and reduction of Claudin-7 in UC patients. Compared to wild-type mice, Mmp7-/- mice had significantly less inflammation in the colon upon DSS insult. DSS-induced alterations in junction proteins were mitigated in Mmp7-/- mice, suggesting that MMP-7 disrupts the intestinal barrier. MMP-7 antibody significantly ameliorated colonic inflammation and Claudin-7 reduction in 2 different rodent models of colitis. Summary: MMP-7 impairs intestinal epithelial barrier by cleavage of Claudin-7, and thus aggravating inflammation. These studies uncovered Claudin-7 as a novel substrate of MMP-7 in the intestinal epithelium and reinforced MMP-7 as a potential therapeutic target for IBD.